Preparation and Performance of Capric-Myristic Acid Binary Eutectic Mixtures for Latent Heat Thermal Energy Storages. (19th August 2019) - Zhou, Dongyi; Zhou, Yuhong; Liu, Yicai; Luo, Xianzhi; Yuan, Jiawei
Abstract : The capric-myristic acid (CA-MA) binary eutectic mixture phase change material (PCM) was prepared for low-temperature latent heat thermal energy storage (LHTES). The thermal properties, thermal stability, and long-term cycling reliability of the PCMs were measured. Differential scanning calorimetry results showed that the CA-MA binary eutectic mixture at the mass ratio (72/28 wt%) indicated a high-performance PCM for its suitable phase change temperature (T m : 18.21°C, T f : 17.40°C) and high latent heat (H m : 148.5 J/g, H f : 134.0 J/g). Thermal gravimetric analysis results indicated that the CA-MA binary eutectic mixture had excellent thermal stability in its operating temperature range. The thermal cycling tests and Fourier transform infrared spectroscopy results revealed that the CA-MA binary eutectic mixture had good long-term cycling thermal chemical reliability. In summary, in terms of thermal property, thermal stability, and reliability, the prepared CA-MA PCM could be applied particularly for low-temperature LHTES systems and backfill materials of ground source heat pump systems.